Pelatihan Pembuatan Pupuk Organik dari Feses Kambing di Dau Malang - Wehandaka Pancapalaga; Suyatno Suyatno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Selorejo village is famous for its sweet orange picking tours, this is because the majority of Selorejo villagers are orange farmers. The problem is to increase the quantity of citrus production, farmers in the village of Selorejo generally use chemical fertilizers while the abundance of goat manure in the village is wasted without being able to process it into compost. The purpose of this community service is to implement science and technology in the form of making organic fertilizer from goat manure as an effort to increase orange production. This activity was carried out in Selorejo Village, Dau District, Malang Regency. The method used in this activity is an education in the form of counseling and training. The results of community service activities are, first, the community has increased knowledge (41.1%) about the importance of organic fertilizer in citrus cultivation. Second, there is an increase in skills (58%) in making organic fertilizer from goat manure. Third There is a change in attitude (49.1%) towards the use of organic fertilizer from goat manure. While the goat manure produced has met SNI standard 19-7030-2004.